A Comparative Analysis on Child Depression Inventory among Islamic Educational Institutions in Malaysia - Siti Hajar, Abdul Rauf (IJRDO - Journal of Social Science and Humanities Research, 2018)
Childhood and adolescent depression commonly emerge within a society and as the affected children grows into adulthood, they tend to carry the negative implications of the depression including in school performances, peer relationship and also behavioural functioning. This also indicates that childhood depression is grievous to the mental and cause destructives on child development. This study aims to identify the differences in the level of depression in ‘madrasah’ and ‘pondok’ based on the five factors in Children’s Depression Inventory by Kovacs which are Anhedonia, Negative self-esteem, Ineffectiveness, Interpersonal Problems and also Negative Mood (Gomez and Vance, 2016). The sample of this study consists of 135 respondents from madrasah and 117 respondents from ‘pondok’ which sum up to a total of 252 respondents altogether. The respondents were instructed to complete Children’s Depression Inventory (CDI) questionnaire. A vast number of mental development research have occupied the CDI model to measure childhood depression. The questionnaire was constructed using 5 scales in which it starts with Scale 1 that represents ‘Strongly Disagree’ until Scale 5 that indicates ‘Strongly Agree’. From the result, it can be identified that there are distinguishable differences in the level of depression between madrasah and ‘pondok’. Among five factors of CDI, the only one that shows significant difference between madrasah and ‘pondok’ is interpersonal problems. In conclusion, there is a probability that mental illness might be number one disease in future and can affect the child. Therefore, it is necessary to prevent this from now.